Theoretical density functional study of gas-phase tautomerization and acidity of 5-methylhydantoin and its thio derivatives - Safi, Zaki Sulieman (European Journal of Chemistry, 2012)
Tautomerization and acidities of various 5-methylhydantoins and their thio derivatives were predicted using Density Functional Theory (DFT). The functional used was B3LYP and the basis set for all atoms was 6-311+(d,p). Single point energy computations were performed at the 6-311+G(2df,2p) basis set. The relative stabilities of the different tautomers of the 2,4-dioxo, 2-thio-4-oxo, 4-thio-2-oxo and 2,4-dithio derivatives of the deprotonated 5-methylhydantoin have been studied. In all cases, the most stable deprotonated conformers are the oxo-thione, the dioxo or the dithio. As for the neutral and the protonated 5-methylhydantoin-thio derivatives, the tautomerization activation barriers are high enough as to conclude that the oxo-thione structures should be found in the gas phase. It was revealed that the ring-nitrogen atom at position 3 (N3) is more acidic than that at position 1 (N1), hence 5-methylhydantoin thio derivatives in the gas phase are an N3-acid. It has been found that the 2,4-dithio species is the most acidic compound among all the investigated compounds. The acidity values were found to be 343 (2O4O), 337 (2S4O), 336 (2O4S) and 332 kcal/mol (2S4S).